Inhibitive Kinetic Spectrophotometric Determination of Protein Using Sulfonazo(III)-Potassium Periodate System - Li, Jing-Mei; Zhang, Chuan-Ping; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2010)
Quantitative analysis of protein is often involved in biochemistry and other biological disciplines. It is also an important indicator of clinical laboratory diagnosis of diseases and checking the treatment effect, but also the test item of separation and purification of many biological drugs in food quality testing and analysis. This paper puts forward a new method of kinetic spectrophotometric determination of protein based on the principle that potassium periodate oxidizes sulfonazo(III) fading in the Clark-Lubs buffer medium at pH 2.2 and bovine serum albumin has an inhibitive effect on this reaction. The maximum absorption wavelength of system is 570 nm. The absorbance difference (DA) is linearly related with the concentration of bovine serum albumin over the range of 2-48 μg/mL and fitted the equation: DA = 0.0307 C (C: μg/mL) + 0.1781, with the correlation coefficient of 0.9930. The detection limit of the method was 1.6 μg/mL. The method has been successfully used to determine protein content in soybean milk and soybean powder samples, with the relative standard deviations of 3.32 and 1.70 % calculated from 11 determinations. Method recoveries were 102.3 and 102.5 %, respectively.